Use of Microcomputer Technology in electronic toll systems - NOVÁK, Daniel; PAVLOVKIN, Ján; NOVÁK, Viktor (Journal of Education, Technology and Computer Science, 2013)
The study deals with the use of information technology for road pricing. It characterizes the basic technological solutions of electronic fee collection systems, it specifies their technical attributes and it gives examples of their use in practice. A special part of the study is devoted to add-on telematic applications. Finally the two main fee collection systems are compared and their strengths, weaknesses and also the economic aspects are pointed out.